Strategi Percepatan Pengumpulan Data Yuridis Dalam Pendaftaran Tanah Sistematis Lengkap di Desa Palbapang Kecamatan Bantul Kabupaten Bantul - Mrs Harfianty; I Gusti Nyoman Guntur; Harvini Wulansari (Sekolah Tinggi Pertanahan Nasional, 2020)
Complete Systematic Land Registration (PTSL) is a government program in accelerating mass land registration with a complete map concept. This program is expected able to overcome the delays of previous mass land registration program through the scheme of ajudication and PRONA. To achieve the goals, throughout the year, the target is high and always increase. Because of this high target, Land Office in Bantul District implement some innovations, especially in juridical data collection. This research aimed to explain the strategy in collecting juridical data in Palbapang Village, and find obstacles in data collection. Qualitative descriptive research was used for this research. The results of the research showed that: 1) the strategies used by Land Office is the use of SIAP application for juridical data input and involved several teams in the collection of juridical data such as puldatan team, village government and the community; 2) there are constraints on the implementation, including lack of human resources in carrying out tasks as a juridical task force, and there were still many villages that collect documents near the end of the fiscal year.